Hearing Outcomes According to the Types of Mastoidectomy: A Comparison between Canal Wall Up and Canal Wall Down Mastoidectomy - Kim, Min-Beom (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2010)
OBJECTIVES: The aim of this study was to compare the hearing outcomes between canal wall up mastoidectmy (CWUM) and canal wall down mastoidectmy (CWDM). METHODS: One hundred seventy one chronic suppurative otitis media (CSOM) patients were enrolled in this retrospective study. The patients who underwent the second staged ossiculoplasty at least 6 months after mastoidectomy and who had an intact, well aerated tympanic cavity as well as intact mobile stapes at the time of operation were selected from the medical record. Based on the type of mastoid surgery, the patients were categorized into two groups: the CWUM (n=38) and CWDM groups (n=133). The hearing results of the CWUM and CWDM groups were compared using the pre- and post-operative air-bone gap (ABG) at 3 months after ossiculoplasty. RESULTS: The preoperative ABG in both groups (CWUM and CWDM) were 28.4±15.6 dB and 31.8±14.5 dB, respectively (P=0.18). Both groups didn't show any significant difference (10.9 dB vs. 13.5 dB, respectively) (P=0.21) for the postoperative ABG closure. The proportion of patients with an ABG less than 20 dB was 58.6% of the CWDM patients and 68.4% of the CWUM patients (P=0.25). CONCLUSION: The type of mastoid surgery (CWUM and CWDM) did not affect the hearing results of CSOM patients. When choosing the type of mastoidectomy procedure for CSOM surgery, the hearing outcomes are basically the same for both types of procedure.